AN INVESTMENT FEASIBILITY ANALYSIS FOR THE DEVELOPMENT OF HOTEL X IN MATARAM - Daffa Abiyyu Achmad; Kusuma Ratnawati (CV KULTURA DIGITAL MEDIA, 2026)
The objective of this research is to analyze investment feasibility in the development of Hotel X in Mataram using three scenarios: base case, weak case, and best case. The method of analysis covers the calculation of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Profitability Index, as well as sensitivity analyses on investment value changes and WACC on NPV and IRR. The analysis results for the base case scenario indicate that this investment is feasible with the NPV of IDR 15,400,833 thousand, the IRR of 14.2%, payback period of ten years, and the profitability index of 1.6; which are considered as not feasible. In the weak case scenario, the NPV is negative at IDR 1,815,997 thousand with the IRR of 11.58%, payback period of twelve years, and profitability index of 1.6, which is also not feasible. For the best-case scenario, the NPV reaches IDR 35,301,509 thousand with the IRR of 16.86%, the payback period of nine years, and the profitability index of 1.4, which shows significant earnings potentials. He sensitivity analyses indicate that the investment value changes and WACC have significant impacts on NPV and IRR. Further, the results of the sensitivity analyses on the three scenarios demonstrate that the investment feasibility in the development project of Hotel X in Mataram is highly dependent on the investment value and WACC. The sensitivities indicate that this project has a strong potential to succeed under normal or optimal economic conditions and capital costs, but risks may appear if the conditions get worse. In general, based on the financial and sensitivity analyses, the development project of Hotel X in Mataram is feasible in several scenarios.